Effect of seed transmitted Bipolaris sorokiniana on the growth and survival of wheat seedlings - RASHID, A.Q.M. BAZLUR (Indian Phytopathology, 2002)
The effect of seed transmitted B. sorokiniana [Cochliobolus sativus] on the growth and survival of wheat seedlings was studied in vitro. Seed germination and seedling emergence were affected, resulting in pre- and post- emergence blights or malformed, dwarf and spindly growth. The infected seedlings sprouted irregularly, sometimes earlier than the healthy ones. Infection severity increased significantly with increased seedling age but no significant difference was observed between disease incidenceat 28 days (76.6%) and at 21 days (71.2%). Regressions of infection severity on different growth characteristics showed the highest positive relationship with seedling age. Up to 63.85% of seedlings were affected within 21-28 days.